Fatal heart block from intentional yew tree (Taxus baccata) ingestion: a case report. Issue 1 (23rd December 2019) - G., Natasha; Chan, Mark; Gue, Ying X; Gorog, Diana A
Abstract: Background : Taxus baccata, also known as English yew, is a poison that causes cardiac arrhythmias and can result in death from cardiogenic shock. Case summary : A 49-year-old gentleman was admitted following yew ingestion with suicidal intent. He was bradycardic at 30 b.p.m. and hypotensive on arrival. Electrocardiography revealed complete heart block with broad complex ventricular escape rate of 30 b.p.m. Bedside echocardiography revealed severe global impairment of right and left ventricular systolic function. Urgent temporary transvenous pacing was instituted, and the patient was considered for veno-arterial extracorporeal membrane oxygenation. Unfortunately, he deteriorated rapidly and cardiorespiratory arrest ensued, and despite prolonged in-hospital resuscitation, the patient died. Post-mortem examination revealed small needle-shaped plant leaves together with seeds found in the stomach. Ante mortem serum sample analysis sent to the Royal Botanical Gardens and revealed the presence of taxine Type B alkaloids in the patient's blood. Discussion : Yew poisoning is a rare occurrence, and there is currently no effective antidote. Treatment involves supportive management, comprising prolonged effective cardiopulmonary resuscitation, pacing, and mechanical cardiac support. This case illustrates the importance of prompt recognition of yew poisoning, alongside early consideration of pacing and mechanical cardiac support. Due to the rarity of this cause of heart block, and since patients may not always volunteer a history of yew ingestion, yew poisoning is something that physicians should be aware of and this should be considered in the differential diagnosis in patients with unexpected heart block. Serum analysis for taxine alkaloids can be used to confirm the diagnosis.